PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM TIRTA TUAH BENUA KUTAI TIMUR CABANG SANGATTA UTARA - Adi Suroso, Herry Mulyana, Titin Ruliana (EKONOMIA, 2016)
The purpose of this study is : To determine the quality of service to customer satisfaction on PDAM Tirta Tuah Continent East Kutai Sengata Branch . Based on the research results obtained include several variables X1 Tangible , Reliability X2 , X3 Resvonsiveness , Assurance X4 , X5 Emphathy . Measuring the level of customer satisfaction with service Qualityyang models developed by Parasuraman , Zeithaml , and Berry , 1990 consists of five dimensions: Tangible , Reability , Responsiveness , Assurance , and Empathy.Sedangkan to know how much the relationship between the independent variable review of customer satisfaction taps , performed by finding the regression equation .       The results measure the level of customer satisfaction with the method of Service Quality , in general shows are not satisfied ( 50.20 % ) . Where Responsiveness aspect gives the most impact on customer satisfaction levels compared with other variables taps of 0.708 . Thus the hypothesis states that the variable quality of the Tangible , Reability , Responsiveness , Assurance , and Empathy shows results not satisfied ( 50.20 % ) , based on the analysis of SPSS aspects Resvonsiveness the greatest impact on customer satisfaction